Bloom of the two dinoflagellates Ceratium furca and Diplopsalis lenticula in a mangrove estuary of Thailand - Tatsuya Yurimoto; Dusit Aue-umneoy; Chonlada Meeanan; Isao Tsutsui (My University, 2015)
Knowledge of the planktonic species that appear in mangrove estuaries in tropical areas is still poor. We believe that case report data on the appearance of species is important for clarifying the ecosystem of the mangrove estuary. We report in this paper on the occurrence of blooms and discuss the factors that influence blooming, based on an observed bloom consisting of two dinoflagellates in the mangrove estuary of Samut Songkhram, Thailand, in December 2012. From fluorescence microscopic observation of the armors of the dinoflagellates after calcofluor white staining, we identified these dinoflagellates as Ceratium furca and Diplopsalis lenticula. In addition, from the annual data on air temperature and precipitation for that year, it was found that the bloom occurred in early dry season. Additionally, diatoms that inhibit the growth of dinoflagellates were observed at low densities. These results suggested that the two dinoflagellates, C. furca and D. lenticula, grew during disappearance of diatoms.
Keywords: Dinoflagellate; Bloom; Red tide; Marine and coastal ecosystems